The Holocaust in the Romanian borderlands - Poliec, Mihai I. (Milton Park, Abingdon, Oxon : New York, NY)
1 online resource
Keywords: This volume examines the changing role which ordinary members of society played in the state-sponsored persecution of the Jews in Bukovina and Bessarabia, both during the summer of 1941, when Romania joined the Nazi invasion of the Soviet Union, and beyond. It establishes different patterns of civilian complicity and discusses the significance of the phenomenon in the context of the exterminatory campaign pursued by the Romanian military authorities against the Jews living in the borderlands.